2014
DOI: 10.1253/circj.cj-14-0099
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Survey of Catheter Ablation for Atrial Fibrillation: The Japanese Catheter Ablation Registry of Atrial Fibrillation (J-CARAF)

Abstract: Background: A nationwide survey of catheter ablation for atrial fibrillation (AF) was conducted in Japan to determine the mid-term performance of the therapy from analysis of the 1-year outcome of registered patients. Methods and Results:A total of 2,137 patients who underwent AF ablation in September 2011 and March 2012 were initially registered. In 2013, the 1-year follow-up data of 1,208 patients (56.5% of 2,137) from 119 centers were collected. Average age was 61.9±10.7 years. Patients with paroxysmal AF (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 20 publications
4
26
1
Order By: Relevance
“…Our results are comparable with these reported in other registries [5,6]. Shah et al [5] identified 22% AF readmission rate and almost 40% rehospitalization rate in AF ablation patients in California in a 1-year follow-up.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results are comparable with these reported in other registries [5,6]. Shah et al [5] identified 22% AF readmission rate and almost 40% rehospitalization rate in AF ablation patients in California in a 1-year follow-up.…”
Section: Discussionsupporting
confidence: 90%
“…In the same study, 30-day all-cause readmission rate was 10%. In the J-CARAF study, ablation was successful in approximately 70% of paroxysmal AF patients and 60% of non-paroxysmal AF in a 1-year after the index procedure [6].…”
Section: Discussionmentioning
confidence: 99%
“…Precise information on AAD therapy will be reported in another article. 10 In this survey, the number of patients who had paroxysmal AF attack less than once per month but who received ablation increased significantly during the survey period (Figure 1). This might indicate that application of AF ablation was expanding to patients with infrequent paroxysmal AF attacks.…”
Section: Af Ablation Patientsmentioning
confidence: 77%
“…In the last decade, radiofrequency catheter ablation (RFCA) has achieved satisfactory results, and stable sinus rhythm without any antiarrhythmic drugs can be maintained in up to 50-60% of patients with persistent AF during mid-to long-term follow-up [2,3]. Furthermore, LA reverse remodeling is often seen when stable sinus rhythm is achieved [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%